Tillering Capacity of Brachiaria Cultivars in the Brazilian Semi-Arid Region During the Dry Season - E. L. L. Véras; G. S. Difante; A. L. C. Gurgel; C. M. Costa; J. V. Emerenciano Neto; J. G. Rodrigues; A. B. G. Costa; M. G. Pereira; L. C. V. Ítavo (Faculty of Animal Science, Bogor Agricultural University, 2020)
Identifying forage species that are responsive in regions with marked water deficits is one of the greatest challenges for the sustainable development of agriculture. However, information is still lacking about the persistence response of those pastures and their abilities to produce new tissues at the times of water scarcity. We hypothesized that Brachiaria grass has a tillering capacity during water-stress periods. This study thus examined the tillering capacity and structural characteristics of four Brachiaria brizantha cultivars (Xaraés, Piatã, Marandu, and Paiaguás) and one Brachiaria decumbens cultivar (Basilisk) in the Brazilian semi-arid region during the dry season (September to March). The experiment was laid out in a randomized block design with repeated measures over time in which five treatments were tested in four replicates. Tillering parameters, pasture production, and structural variables were evaluated. There was no interaction effect of cultivar × evaluation period on the tiller appearance (p= 0.1774), mortality (p= 0.1952) or survival (p= 0.4469) rates. The highest tiller appearance and mortality rates were observed in Marandu, while the highest survival rates were found in Marandu and Paiaguás. The index of tiller population stability was higher than or equal to 1.0 in all cultivars. Cultivar Basilisk showed the highest herbage mass yield (4448.0 kg DM ha-1), whereas Basilisk exhibited the highest yields of leaf (1845.9 kg DM ha-1), stem (1676.9 kg DM ha-1), and dead material (925.2 kg DM ha-1). The highest leaf:stem ratio (1.8) was found in Marandu. Cultivar Xaraés had the highest canopy (70.8 cm). The B. brizantha and B. decumbens cultivars evaluated in this study have the potential for cultivation in areas with marked water deficits, as is the case of the Brazilian semi-arid region. Cultivars Marandu, Basilisk, and Paiaguás exhibited the greatest tillering dynamics as well as the highest herbage-mass yield.